OTHR-39. Extraneural spreading of a diffuse leptomeningeal glioneuronal tumor in a child: patient-derived models show sensitivity to vinblastin and trametinib. (3rd June 2022) - Messiaen, Julie; Claeys, Annelies; Shetty, Aniket; Spans, Lien; Derweduwe, Marleen; Uyttebroeck, Anne; Depreitere, Bart; Bempt, Isabelle Vanden; Sciot, Raf; Ligon, Keith; Jones, David; Jacobs, Sandra; et al.
Abstract: Diffuse leptomeningeal glioneuronal tumors (DLGNT) are rare neoplasms of the central nervous system. We describe the generation of patient-derived models from a DLGNT that metastasized to the peritoneal cavity via a ventriculoperitoneal shunt in a child. The original tumor contained a KIAA1549:BRAF fusion with a chromosome 1p deletion and corresponded with methylation subclass DLGNT-MC-2 From a sample of ascitic fluid, metastatic tumoral cells could be extracted and expanded ex vivo into a long-term cell culture model. This patient-derived cell line (PDCL) showed mixed morphological phenotypes and expressed MAP2 and SYP. The KIAA1549:BRAF fusion was preserved and the PDCL still corresponded to the original methylation subclass DLGNT-MC-2. Whole-genome sequencing showed additional mutations potentially contributing to the malignant behavior of the tumor. Cytotoxic assays performed on the PDCL indicated high sensitivity to vinblastine and trametinib (MEK-inhibitor) and intermediate sensitivity to DRD/ClpP-modulators. The PDCL underwent viral transduction to induce GFP-fLux positivity and was intraperitoneally injected into immunocompromised mice. A mouse model could be generated, with the growth of a peritoneal tumor in a localized manner. The cells grown from the mouse tumor were again put into culture and were afterwards subjected to the same treatments as the PDCL. This confirmed a similar profile, with high sensitivity to vinblastin and trametinib and an intermediate sensitivity to the DRD/ClpP-modulators. In conclusion, we were able to generate patient-derived models from a metastatic DLGNT, which recapitulate the molecular characteristics of the original tumor. The models showed high sensitivity to vinblastin and targeted therapy with MEK-inhibition, but further studies are necessary to define the adequate treatment for this kind of tumor.